2020
DOI: 10.1101/2020.12.25.424008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential Dynamic Behavior of Prefusion Spike Proteins of SARS Coronaviruses 1 and 2

Abstract: Within the last two decades, severe acute respiratory syndrome (SARS) coronaviruses 1 and 2 (SARS-CoV-1 and SARS-CoV-2) have caused two major outbreaks. For reasons yet to be fully understood the COVID-19 outbreak caused by SARS-CoV-2 has been significantly more widespread than the 2003 SARS epidemic caused by SARS-CoV-1, despite striking similarities between the two viruses. One of the most variable genes differentiating SARS-CoV-1 and SARS-CoV-2 is the S gene that encodes the spike glycoprotein. This protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 84 publications
(149 reference statements)
1
7
0
Order By: Relevance
“…Advanced membrane technology offers a promising solution in battling COVID-19 variants through hybrid and synergistic functionalities such as photocatalytic oxidation, distillation, and filtration. The COVID-19 variants mainly involve mutations in the gene encoding the spike protein of SARS-CoV-2, which is the major surface glycoprotein that forms the cell wall or capsid of the viruses [173] . For this reason, the ongoing membrane technology can be designed and developed by considering the features of the spike protein of the SARS-CoV-2 virus.…”
Section: Potential Of Membrane Technology For Wastewater Epidemiology Work Especially In Battling Covid-19mentioning
confidence: 99%
“…Advanced membrane technology offers a promising solution in battling COVID-19 variants through hybrid and synergistic functionalities such as photocatalytic oxidation, distillation, and filtration. The COVID-19 variants mainly involve mutations in the gene encoding the spike protein of SARS-CoV-2, which is the major surface glycoprotein that forms the cell wall or capsid of the viruses [173] . For this reason, the ongoing membrane technology can be designed and developed by considering the features of the spike protein of the SARS-CoV-2 virus.…”
Section: Potential Of Membrane Technology For Wastewater Epidemiology Work Especially In Battling Covid-19mentioning
confidence: 99%
“…19,20,[24][25][26] Opening pathways determined using steered MD and targeted MD have been reported. [26][27][28] More recently, extensive simulations using enhanced sampling techniques such as weighted ensemble 29 and fluctuation amplification of specific traits (FAST) adaptive sampling combined with Folding@home 30 have provided details of multiple pathways for the S-protein opening. Moreover, features of the energy landscape of these conformational transitions that are necessary for viral binding and entry are beginning to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 13, 2021. ; https://doi.org/10.1101/2021.08.12.456168 doi: bioRxiv preprint that are necessary for viral binding and entry are beginning to emerge. 27,28,31 A recent study by Amaro and coworkers has highlighted the functional role of glycans at N165 and N234 beyond shielding 24 based on separate equilibrium simulations of the Sprotein down and up states. When the RBD transitions to the up state, the glycan at N234 rotates into the resulting void, stablizing the up conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SARS-CoV-2 is more infectious than SARS-CoV. Besides, mounting evidence showed that the recently discovered SARS-CoV-2 is more infectious than the isolate reported in Wuhan, China in late December 2019, partly due to the conformational changes caused by the spike mutation ( Gobeil et al, 2021 ; Kumar et al, 2020 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The NTD (N-terminal domain) locates at 14–306 amino acids (aa) of the viral spike protein. NTD has obvious structural plasticity, involves prebinding activation and immune activation, and plays vital roles in the effective binding process and immune response together with the RBD domain ( Kumar et al, 2020 ; Liu et al, 2020 ; McCallum et al; Rosa et al, 2021 ). Moreover, the GTNGTKR motif at 72–78 aa of the NTD may be involved in recognizing other receptors/co-receptors besides the ACE2 ( Behloul et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%